Indigenous Fire Knowledge: Benefits, Barriers, and Best Practices Across Four International Cases - France, Kyla (Université d'Ottawa | University of Ottawa, 2024)
This major research paper examines the critical role of Indigenous Fire Knowledge (IFK) in mitigating the effects of climate change, namely wildfires. Today, there is a growing global call to revive IFK to improve wildfire management and uphold Indigenous rights. This study employed a document analysis and case study approach, integrating insights from peer-reviewed and grey literature using a blended coding strategy to inform its findings. Despite identified barriers to mobilising IFK such as societal perceptions of fire, jurisdictional challenges, and resource constraints, the analysis of case studies from the Karuk Tribe, Firesticks Alliance, the Secwépemc Nation, and Indigenous Fire Brigades finds effective approaches to mitigate wildfire impacts through Indigenous fire practices. The paper presents recommendations for Canada that include formal partnerships between governments and Indigenous communities/organizations, supporting bottom-up, Indigenous-led initiatives, and promoting education on IFK and accrediting cultural burning practices. Keywords: Indigenous Fire Knowledge (IFK), wildland fire, knowledge bridging, disaster risk reduction, Indigenous fire stewardship, community, self-determination